2020
DOI: 10.2166/wh.2020.121
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater quality and non-carcinogenic health risk assessment of nitrate in the semi-arid region of Punjab, India

Abstract: Groundwater is the main source of water in the study area (Rupnagar District, Punjab), and its quality is essential since it is the primary determinant of the suitability of groundwater for drinking and irrigation purposes. In this study, data from 28 years have been used to evaluate the adequacy of groundwater for domestic and irrigation purposes and assess the potential human health impacts of nitrate contaminants. Results of sodium adsorption ratio, percentage sodium, magnesium hazard ratio, Kelley ratio, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Previous studies have also indicated GW NO 3 pollution in these areas. 75 , 78 , 159 161 The areas in the southwest and northeast parts predominantly showed lower probabilities of GW NO 3 to be elevated. The risk map generated using the RF model predictions and the cutoff of 0.49 showed the areas exposed to high risk of excess GW NO 3 as well as the low-risk areas in the state ( Figure 4 d).…”
Section: Resultsmentioning
confidence: 96%
“…Previous studies have also indicated GW NO 3 pollution in these areas. 75 , 78 , 159 161 The areas in the southwest and northeast parts predominantly showed lower probabilities of GW NO 3 to be elevated. The risk map generated using the RF model predictions and the cutoff of 0.49 showed the areas exposed to high risk of excess GW NO 3 as well as the low-risk areas in the state ( Figure 4 d).…”
Section: Resultsmentioning
confidence: 96%
“…Water samples were obtained from twelve (12) sampling points. Parameters analysed include pH, Electrical Conductivity (EC), Total Dissolved Solids (TDS), Temperature, Calcium, Magnesium, Potassium, Sodium, Iron, Sulphate, Bicarbonates, Chlorine, Nitrate and Fluoride.…”
Section: Physio-chemical Analysismentioning
confidence: 99%
“…Water Quality Index is a mathematical equation that provides a clear understanding of the quality of surface and groundwater (Chaudhry & Sachdeva, 2020). It is a means of integrating a wide range of information into a simpler form and as such is considered as the most effective tool in water quality assessment (Akter et al, 2016) Step 1: Assigning of weights.…”
Section: Water Quality Indexmentioning
confidence: 99%
“…In this paper, the health risk index was used, which considers chronic daily intake (CDI), the hazard quotient (HQ), and the hazard index (HI) [6,[28][29][30][31][32] and is one of the most widely used methods in various research projects due to its reliability. The majority of studies generally analyze Potentially Toxic Elements (PTE), nitrates, and microbiological parameters separately [33][34][35], but all these factors should be evaluated together when studying springs.…”
Section: Introductionmentioning
confidence: 99%